Stability of prochlorperazine in solution and in the solid-state - Antunes, Edith Martins (Rhodes University, Faculty of Science, Department of Chemistry, 2000)
Prochlorperazine, a member of the piperazine subclass of phenothiazines, widely used as an anti-emetic, is susceptible to oxidation to sulfoxides. These are main metabolites and degradants of all phenothiazines which are found to be inactive at the dopamine receptors. Prochlorperazine causes photosensitivity effects in patients attributed to dechlorination at C2 with the release of HCI (Huang and Sands, 1967; Nejmeh and Pilpel, 1978; Moore and Tamat, 1980). The aim of this study is to investigate the thermal and photostability of prochlorperazine edisylate and mesylate salts in the solid state and in solution. Prochlorperazine is available as a fine chemical and in a variety of dosage forms, including injectables and tablets. According to ICH guidelines, any degradants greater than 0.1 % are required to be isolated and identified. In order to assess the photostability of the two salts, an HPLC method was developed and validated for linearity, accuracy and precision, selectivity, limit of detection, quantitation and ruggedness. Sulfoxides were synthesised for use as standards in the rate studies according to the well-known hydrogen peroxide method (Owens et al., 1989). The rate of prochlorperazine degradation in solution under various light sources (254 nm UV light, diffuse light and sunlight) was studied. The light sources used abovF were quantified using potassium ferrioxalate as a chemical actinometer). The photodegradation rate was found to be greater in ampoules sealed under nitrogen than air, but the thermal degradation was faster in ampoules sealed with air than those purged with nitrogen. Amber ampoules retarded the rate of degradation under all photolytic conditions. This is a vital consideration for the packaging and storage of prochlorperazine in injectables. Degradation was found to occur mainly by first-order kinetics and the degradation rate decreased in the following order: sunlight » UV light 254 nm > fluorescent I diffuse light. Solid state samples, however, were found to be relatively stable to the various light / heat conditions over a 6 month period when compared to prochlorperazine solutions, but still considerably unstable. Thus both storage and packaging is a vital consideration for prochlorperazine injectables. The thermal behaviour of mixtures of prochlorperazine with standard excipients, was assessed for potential interactions, using differential scanning calorimetry. For most of the excipients (magnesium stearate, stearic acid, Explotab®, AC-Di-Sol®, Encompress® and Ludipress®, lactose and Starch 1500®) disappearance or broadening of the melting endotherm of the drug indicated interactions. Lubritab®, however, was the only 'inert' excipient tested. Liquid chromatography - mass spectrometry (LC-MS) was used to determine the nature of the degradation products. The major degradation pathways included dechlorination and demethylation of the parent drug, as well as sulfoxidation and Noxidation. Prochlorperazine underwent dechlorination and sulfoxidation with subsequent photosubstitution to yield the 2-hydroxy derivative. The solid state photostudies showed the formation of dealkylated, oxidised and hydroxylated products, sulfoxides and dimers. Since N-demethylation, N-oxidation, sulfoxidation and aromatic hydroxylation are reported to occur in the in vitro metabolism of perazine derivatives, it does appear that there is some relationship between metabolites and photoproducts (Breyer, 1974). This study has been successful in providing understanding of the photolytic and thermal degradation pathways of prochlorperazine.
Keywords: Phenothiazine